Women and gambling disorder: Assessing dropouts and relapses in cognitive behavioral group therapy - Baño, Marta; Mestre-Bach, Gemma; Granero, Roser; Fernández-Aranda, Fernando; Gómez-Peña, Mónica; Moragas, Laura; del Pino-Gutierrez, Amparo; Codina, Ester; Guillén-Guzmán, Elías; Valero-Solís, Susana; Lizbeth Lara-Huallipe, Milagros; Baenas, Isabel; et al. (Addictive behaviors, 2021)
•The dropouts occurred within the first two months of the treatment.•The dropout risk was higher for women with lower GD severity.•The dropout risk was higher for women with higher psychopathological distress.•The relapses were registered throughout the treatment.•The frequency of relapses was higher for divorced women with non-strategic gambling. Background: Gender-specific literature focused on gambling disorder (GD) is scarce, and women with GD have been understudied. Therefore, the aim of this study was to estimate the short-term effectiveness in women with GD (n = 214) of a group standardized cognitive-behavioral therapy (CBT) and to identify the most relevant predictors of the primary therapy outcomes (dropout and relapse). Methods: The manualized CBT consisted of 16 weekly outpatient group sessions. Women were provided with resources to obtain a better understanding of the GD, to improve self-control and to manage risk situations. Results: The dropout risk was higher for women with lower GD severity and higher psychopathological distress. Among other factors, lower education levels were a significant predictor of the relapse risk and and the frequency of relapses was higher for divorced women with a preference for non-strategic gambling and with substances consumption. Conclusions: Our findings evidence women-specific predictors of the primary therapy outcomes. The results highlight the need to design psychological interventions that address dropout and relapse risk factors in women.